2011
DOI: 10.1016/j.biopsych.2011.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Default-Mode and Task-Positive Network Activity in Major Depressive Disorder: Implications for Adaptive and Maladaptive Rumination

Abstract: Background Major Depressive Disorder (MDD) has been associated reliably with ruminative responding; this kind of responding is composed of both maladaptive and adaptive components. Levels of activity in the default-mode network (DMN) relative to the task-positive network (TPN), as well as activity in structures that influence DMN and TPN functioning, may represent important neural substrates of maladaptive and adaptive rumination in MDD. Methods We used a unique metric to estimate DMN dominance over TPN from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
541
9
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 689 publications
(626 citation statements)
references
References 28 publications
51
541
9
5
Order By: Relevance
“…To investigate whether an alteration in DN connectivity could provide a biomarker of therapy response and to determine brain mechanisms of action underlying sleep deprivations antidepressant effects, we examined its influence on resting state default mode network and DN connectivity in healthy humans. Our findings show that sleep deprivation reduced functional connectivity between posterior cingulate cortex and bilateral anterior cingulate cortex (Brodmann area 32), and enhanced connectivity between DN and distinct areas in right dorsolateral prefrontal cortex (Brodmann area 10). These findings are consistent with resolution of dysfunctional brain network connectivity changes observed in depression and suggest changes in prefrontal connectivity with the DN as a brain mechanism of antidepressant therapy action.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…To investigate whether an alteration in DN connectivity could provide a biomarker of therapy response and to determine brain mechanisms of action underlying sleep deprivations antidepressant effects, we examined its influence on resting state default mode network and DN connectivity in healthy humans. Our findings show that sleep deprivation reduced functional connectivity between posterior cingulate cortex and bilateral anterior cingulate cortex (Brodmann area 32), and enhanced connectivity between DN and distinct areas in right dorsolateral prefrontal cortex (Brodmann area 10). These findings are consistent with resolution of dysfunctional brain network connectivity changes observed in depression and suggest changes in prefrontal connectivity with the DN as a brain mechanism of antidepressant therapy action.…”
mentioning
confidence: 63%
“…Here, we found that sleep deprivation reduced connectivity on the ACC-PCC axis. This is of particular interest because resting-state DMN dominance is associated with increased maladaptive, depressive rumination, and reduced adaptive, reflective rumination (32). Depressed patients typically fail to down-regulate DMN activity during emotional stimulation (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…This inverse relationship between the DMN and CEN is reflected in negative connectivity (or anticorrelations) between these two networks in healthy individuals (Fox et al, 2005;Biswal et al, 2010;Whitfield-Gabrieli and Ford, 2012). DMN-CEN anticorrelations may be altered in MDD (Sheline et al, 2010;Hamilton et al, 2011) and may reflect impairments in attentional control or impulsivity ; however, similar to DMN connectivity, DMN-CEN anticorrelations have scarcely been examined in individuals at risk for, but not yet affected by, depression.…”
Section: Introductionmentioning
confidence: 99%
“…73-118). 16 In effect what Hamilton et al (2011) discovered is that in depressed patients-but not in healthy subjects-greater DMN activity relative to TPN activity correlated with depressive rumination, but not with pondering. This discovery is important because it dovetails neatly with two converging lines of research that might be able to contribute to a theoretically motivated explanation of depression of the sort envisioned by Hempel 50 years ago.…”
Section: Rumination and The Resting State Hypothesis Of Mddmentioning
confidence: 98%
“…The relevance of this distinction between the different types of ruminative cognition to MDD's neural substrate has recently been established by Hamilton et al (2011). The authors discovered that dominance by the brain's "default mode network" (DMN) positively correlates with elevated levels of brooding, but with only low levels of pondering (cf., Hamilton, Chen, & Gotlib, 2013).…”
Section: Rumination and The Resting State Hypothesis Of Mddmentioning
confidence: 99%